Numerical and Experimental Identification of Seven-Wire Strand Tensions Using Scale Energy Entropy Spectra of Ultrasonic Guided Waves - Ji Qian; Xin Chen; Limin Sun; Guowen Yao; Xu Wang (Shock and Vibration)
Accurate identification of tension in multiwire strands is a key issue to ensure structural safety and durability of prestressed concrete structures, cable-stayed bridges, and hoist elevators. This paper proposes a method to identify strand tensions based on scale energy entropy spectra of ultrasonic guided waves (UGWs). A numerical method was first developed to simulate UGW propagation in a seven-wire strand, employing the wavelet transform to extract UGW time-frequency energy distributions for different loadings. Mode separation and frequency band loss of L(0,1) were then found for increasing tension, and UGW scale energy entropy spectra were extracted to establish a tension identification index. A good linear relationship was found between the proposed identification index and tensile force, and effects of propagation distance and propagation path were analyzed. Finally, UGWs propagation was examined experimentally for a long seven-wire strand to investigate attenuation and long distance propagation. Numerical and experimental results verified that the proposed method not only can effectively identify strand tensions but can also adapt to long distance tests for practical engineering.